2002
DOI: 10.1176/appi.ps.53.7.879
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Self-Report of Health Service Use by Individuals With Serious Mental Illness

Abstract: The purpose of this study was to determine whether individuals with serious mental illness could consistently report their use of medical services. Twenty-nine individuals with schizophrenia completed a test-retest protocol using a modified version of the Medical Expenditure Panel Survey; there was a one-week interval between the two administrations of the instrument. Consistency of reporting was generally strong and was strongest for items indicating whether a service had been used in the past six months, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 9 publications
2
70
0
Order By: Relevance
“…Second, because our outcome measure was constructed with self-reported data, our findings may not reflect true use. Although this is a valid concern, evidence suggests that people with severe mental illness provide reliable data (34), and no evidence exists that reliability varies by race-ethnicity. Third, although our state-stratified analyses controlled for state policies that may contribute to disparities, the study was not powered to control for study site (that is, ACT team).…”
Section: Discussionmentioning
confidence: 99%
“…Second, because our outcome measure was constructed with self-reported data, our findings may not reflect true use. Although this is a valid concern, evidence suggests that people with severe mental illness provide reliable data (34), and no evidence exists that reliability varies by race-ethnicity. Third, although our state-stratified analyses controlled for state policies that may contribute to disparities, the study was not powered to control for study site (that is, ACT team).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of studies have found that this approach is acceptable. 72,73 Although routine data sources can be used for some service-use measures, it is not always apparent that these are in themselves wholly accurate measures of resource use. We measured service use over a relatively short period prior to each follow-up and there is no reason to expect that under-or (maybe less likely) over-reporting would affect one group more than another.…”
Section: Cost-effectiveness Of the Dialog+ Interventionmentioning
confidence: 99%
“…Although literature suggests patients with schizophrenia can reliably report their use of health services, including 6-month recall (Goldberg et al, 2002), this 90-day period was half the length of our intervention (6-months). Thus, it is not clear how many participants from the FAST and control conditions used emergency services during the first 3-months of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…For each service, frequency and duration of use over the past 90 days was recorded, as was the reason for the service being used (e.g., physical problem, mental health problem). Previous literature indicates that persons with schizophrenia can provide reliable information about their use of health services, even up to 6-month recall (Goldberg, Seybolt, & Lehman, 2002). Because the present study focused on "emergency" service utilization, the following 4 items from the Intensive Services subscale were used: a) emergency room visit, b) crisis team visit, c) partial hospitalization program, and d) inpatient hospitalization.…”
Section: Methodsmentioning
confidence: 99%